The “First Fruit” of Owambo. Public Story of Nanguroshi/Eeva Maria in the Promotion of Finnish Mission Work - Koivunen, Leila (Suomalaisen Kirjallisuuden Seura, 2025)
This chapter examines how the public story of an Aawambo girl was constructed and used among the Finnish mission community. Nanguroshi, a foster child of a Finnish missionary family, was brought to Finland in 1875, baptised and renamed Eva Maria and sent back to Africa in 1879. The christening marked an important milestone for the Finnish Missionary Society (FMS). It made Nanguroshi a symbol of Finnish efforts in Africa or the ‘first fruit of Owambo’ as she was called. The chapter focuses on mechanisms by which it was hoped that promotional efforts, closely related to Western colonial worldviews, would be able to generate donations and support for mission work. The process whereby Finnish mission supporters became aware of the girl was not, however, straightforward but quite paradoxical in many ways. The two phases identified here – before and after her departure from Finland – clearly reflect different attitudes as regards her utilisation for publicity purposes. The initial plans to make use of her corporeal presence in Finland to gain attention to the work being carried out in Africa proved challenging from the outset, and she was mostly concealed from the curious gaze of mission friends. With her departure, however, she became a celebrated symbol of the success of Finnish mission work abroad. She became a print product whose story was easily available. The public image of Nanguroshi/Eva Maria was not in her own hands. Her story was told by utilising textual elements and references familiar from colonial contexts. Her voice was taken into use to thank the Finns for their involvement in Africa, convince them of the legitimacy of their deeds and thoughts and encourage them to continue.
Colonial Aspects of Finnish-Namibian Relations, 1870–1990: Cultural Change, Endurance and Resistance